Disrupting colonialist language to find knowing in praxis. Cultural Foregrounding and Intra-face. - Hipplewith, Joanne (Murmurations: Journal of Transformative Systemic Practice, 2023)
This paper offers a first-person, post-positivist qualitative study of what race means to me as an individual, professional and systemic practitioner attempting to inhabit decoloniality. I explore how systemic teaching methods fail to open up spaces for exploring cultures during training which leaves trainees, tutors and clients vulnerable to the cultural dominance of western societies and to the marginalisation of Other cultures. I present the conceptual terminology of i) “cultural foregrounding” and ii) “intra-face” to illustrate political and societal discourses about Otherness (colonised and marginalised) in a posthuman and, hopefully, a decolonised world. I show and discuss my internal struggles, cultural reflexivity in writing about my experiences as a colonised Other. This writing is part of a process of decolonising my many selves. On this journey, I travel with a range of scholars who connect with my research and enrich my writing journey. Three sections make up the paper. The first section examines the language of race as a social and political construct. In the second section, I introduce and discuss cultural foregrounding and intra-face. In the final section, I discuss praxis and a working definition of culture. In each of these sections I thread connections to practice.